1992
DOI: 10.4319/lo.1992.37.6.1280
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in lipid content and composition in the benthic amphipods Monoporeia affinis and Pontoporeia femorata

Abstract: Seasonal variation in lipid content and composition was studied in deposit-feeding amphipods from a Baltic archipelago. In Monoporeia afinis, which is more active and has a higher respiration rate, lipid levels were low in winter and early spring, rose to 27% of the dry mass in late summer, then declined in autumn. In Pontoporeia femorata, which regulates its oxygen consumption, lipid levels were 20-23% of the dry mass. In October, maturing male P. fimorata had a significantly lower lipid content than females.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
78
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 22 publications
7
78
4
Order By: Relevance
“…This indicates that densitydependent control of Monoporeia affinis population size through competition for food (Sarvala 1986, Maximov 1997, especially as such competition reduces recruitment success, is a valid hypothesis for explaining the interannual variations in this amphipod population. Corroborating this interpretation, the negative effect of a high density, and of the presence of older generations, on the survival and growth of the young-of-theyear of M. affinis has been experimentally demonstrated by Hill (1992).…”
mentioning
confidence: 97%
“…This indicates that densitydependent control of Monoporeia affinis population size through competition for food (Sarvala 1986, Maximov 1997, especially as such competition reduces recruitment success, is a valid hypothesis for explaining the interannual variations in this amphipod population. Corroborating this interpretation, the negative effect of a high density, and of the presence of older generations, on the survival and growth of the young-of-theyear of M. affinis has been experimentally demonstrated by Hill (1992).…”
mentioning
confidence: 97%
“…Jonasson 1972;Kajak 1988) and lipid dynamics (e.g. Gardner et al 1985;Hill et al 1992). Moreover, interannual variation in the magnitude of diatom input to profundal communities may strongly affect macroinvertebrate life histories (Johnson and Wiederholm 1992).…”
mentioning
confidence: 99%
“…due to environmental change, may have drastic effects on the benthic community. The differences in amphipod response between treatments were greater in terms of weight than in terms of area and demonstrate the ability of amphipods to respond to differences in food source in terms of weight and lipid gain, as reported by Hill et al (1992). The amphipods had the ability to respond to the higher primary production in the A-webs after the light acclimatisation period.…”
mentioning
confidence: 63%
“…If the gonads remain unfertilized, they will degenerate and the females will die, resulting in a lost generation. In addition, it has been suggested that M. affinis needs to reach a threshold size (Leonardsson et al 1988) or achieve a threshold lipid ratio of at least 20% to be able to reproduce (Hill et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation